2016
DOI: 10.1073/pnas.1613058113
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous nonlinear elasticity enables positive mechanical feedback between cells and ECMs

Abstract: In native states, animal cells of many types are supported by a fibrous network that forms the main structural component of the ECM. Mechanical interactions between cells and the 3D ECM critically regulate cell function, including growth and migration. However, the physical mechanism that governs the cell interaction with fibrous 3D ECM is still not known. In this article, we present single-cell traction force measurements using breast tumor cells embedded within 3D collagen matrices. We recreate the breast tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
282
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 297 publications
(321 citation statements)
references
References 64 publications
19
282
0
Order By: Relevance
“…As previous studies have shown that cells are influenced by the presence of fibers [50], a second major goal of this research was to develop a material where fiber density could be manipulated. Fibers not only provide biological cues to embedded cells, but also act as a source of non-linear elasticity within the scaffold, with the capacity to uniquely influence cell-cell communication and alignment [51], as well as the degree of cell contraction [52]. Collagen-mimetic peptides that reproduce a portion of the native collagen triple helix have been incorporated into synthetic scaffolds [53, 54], but these peptides cannot organize to form a fibrillar structure.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have shown that cells are influenced by the presence of fibers [50], a second major goal of this research was to develop a material where fiber density could be manipulated. Fibers not only provide biological cues to embedded cells, but also act as a source of non-linear elasticity within the scaffold, with the capacity to uniquely influence cell-cell communication and alignment [51], as well as the degree of cell contraction [52]. Collagen-mimetic peptides that reproduce a portion of the native collagen triple helix have been incorporated into synthetic scaffolds [53, 54], but these peptides cannot organize to form a fibrillar structure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, by decreasing the gelation temperature, the matrix critical strain (« cr ) decreases (40)(41)(42). Also, at certain gelation temperatures (for example, 37°C), increasing collagen concentration increases the critical strain (« cr ) (41,43). Therefore, we can use our model to predict the shape of the cells, at different levels of « cr and n. As shown in Fig.…”
Section: Cells Are More Elongated In Matrices With Lower Critical Strmentioning
confidence: 98%
“…This is not surprising because tumor and stromal cells are known to actively pull onto the ECM, and thereby remodel the ECM architecture 66, 77, 78 . Collagen bundles have been reported to align perpendicularly to the tumor periphery, possibly by active tumor and stromal cell contraction, facilitate collective tumor cell invasion and correlate with malignancy 79, 80 .…”
Section: Biophysical Drivers In Tumor Cell Invasionmentioning
confidence: 99%